Adipocyte Atrophy Mimicking Signet Ring Cell Carcinoma of the Gallbladder. (31st October 2021) - van Haeringen, Benjamin; Francis, Leo; Olive, Emily; James, Daniel
Abstract : Signet ring cell morphology may result from a variety of causes and ranges from a benign reactive phenomenon to being indicative of highly aggressive malignancy. Benign epithelial signet ring cell change is well described in a variety of tissues, but nonepithelial signet ring cell change is a rare morphologic adaptation of adipose tissue principally described in the setting of cachexia. The location of these atrophic adipocytes outside the plane of normal epithelial layers may raise concern for invasive or metastatic malignancy, and consideration of a benign reactive process is critical to avoid catastrophic overdiagnosis and overtreatment. Further, this change is itself associated with significant mortality related to the underlying cachexia and may be important to highlight to treating clinicians. Compared to malignant signet ring cell carcinoma, benign signet ring cell change is more likely to retain normal lobulated architecture without mass formation, lack significant atypia, have myxoid stroma with a prominent capillary network, and show positive staining S100 protein with negative staining for cytokeratins and mucin. To our knowledge, we present the first described case of nonepithelial signet ring cell change involving the gallbladder, detected as an incidental finding following routine cholecystectomy in an elderly cachectic man.